2017
DOI: 10.1371/journal.pone.0175773
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of quantitative trait loci associated with resistance to net form net blotch (Pyrenophora teres f. teres) in a doubled haploid Norwegian barley population

Abstract: Barley net blotch caused by the necrotrophic fungus Pyrenophora teres is a major barley disease in Norway. It can cause grain shriveling and yield losses, and resistance in currently grown cultivars is insufficient. In this study, a set of 589 polymorphic SNP markers was used to map resistance loci in a population of 109 doubled haploid lines from a cross between the closely related Norwegian cultivars Arve (moderately susceptible) and Lavrans (moderately resistant). Resistance to three net form net blotch (P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…The locus associated with resistance to the S10.2 isolate included one suggestive SNP (JHI-Hv50k-2016-74407) mapped in the interval 23.3-23.8 cM. We suggest that seedling resistance to the S10.2 isolate is conferred by a previously known locus mapped earlier by Wonneberger et al (2017) [7] and Vatter et al (2017) [18] (Table 5). The locus on chromosome 2H revealed for the P3.4.0 isolate included 7 SNPs and was expanded between JHI-Hv50k-2016-104508 and JHI-Hv50k-2016-104859 markers located in the interval 71.0-74.1 cM.…”
Section: Chromosome 2hsupporting
confidence: 53%
See 2 more Smart Citations
“…The locus associated with resistance to the S10.2 isolate included one suggestive SNP (JHI-Hv50k-2016-74407) mapped in the interval 23.3-23.8 cM. We suggest that seedling resistance to the S10.2 isolate is conferred by a previously known locus mapped earlier by Wonneberger et al (2017) [7] and Vatter et al (2017) [18] (Table 5). The locus on chromosome 2H revealed for the P3.4.0 isolate included 7 SNPs and was expanded between JHI-Hv50k-2016-104508 and JHI-Hv50k-2016-104859 markers located in the interval 71.0-74.1 cM.…”
Section: Chromosome 2hsupporting
confidence: 53%
“…First, this locus was found by Steffenson et al (1996) [3], then confirmed by Manninen et al (2006) [27] and named RPt5. Wonneberger et al (2017) [7] and Afanasenko et al (2014) [2] revealed the genomic region associated with NFNB resistance in the same interval. Further loci were revealed close to this region [5,16] ( Table 5).…”
Section: Chromosome 6hmentioning
confidence: 94%
See 1 more Smart Citation
“…k) and Spt1.k (previously rpt5.r ) from CI5791/CI9819, Kombar and Rika, respectively (Abu Qamar et al , ; Koladia et al , ; Manninen et al , , ; Richards et al , ) (Table ). Additional loci that may also be part of the Rpt5 locus and therefore contain additional alleles include QRpts6L , QRpt6 , AL_QRptt6‐1, Rpt‐Nomini and Rpt‐CIho2291 in Halcyon (Raman et al , ), TR251 (Grewal et al , ), Lavrans (Wonneberger et al , ), Nomini and CIho2291 (O’Boyle et al , ), respectively (Table ), as well as undesignated QTLs from Steptoe (Steffenson et al , ), HOR 9088 (Richter et al , ), Kaputar, ND11213 (Cakir et al , ; Emebiri et al , ; Liu et al , ), Chevron (Ma et al , ), SM89010 (Friesen et al , ), M129 (St. Pierre et al , ), Baudin (Cakir et al , ), WPG8412, Pompadour, Stirling (Gupta et al , ), Falcon (Islamovic et al , ), H602 (Hisano et al , ) and UVC8 (Martin et al , ) (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…In same study they found that 4H and 5H chromosomes also carry QTLs that confer resistance against net form of net blotch but in another DH population. Similarly, Wonneberger et al (2017) using a set of 589 polymorphic SNP markers mapped resistance loci in a population of 109 doubled haploid lines from a cross between Norwegian cultivars Arve and Lavrans. Three to four quantitative trait loci (QTL) associated with resistance to net blotch in the seedling stage were found per isolate used.…”
Section: Introductionmentioning
confidence: 99%